CRYPTOGRAPHIC PROTOCOL SECURITY IN NATIONAL ENCRYPTION APPLICATIONS - Widodo, Agung; Suryanto, Yohan (Informatika, Universitas Jenderal Soedirman, 2023)
In the era of digital transformation, information exchange, especially confidential and strategic information has become the most vital aspect for almost all organizations. Various bad precedents regarding classified and strategic information leaks in Indonesia have become a slap in the face that must be acknowledge and answered with effective solutions. In 2020, XYZ Agency developed a file encryption application (ABC Application) to address the challenge of securing confidential information, especially those transmitted on electronic channels. Until 2022, the ABC Application has been implemented in a limited scope and its implementation is planned to be expanded nationally. After 2 years of operation, the XYZ Agency has conducted a study on the security of the algorithm used in ABC Application, but unfortunately has not conducted an in-depth study regarding the security of the protocol suite used in the Application. In this research, a security analysis of ABC application protocol suites, namely the registration protocol, user verification, key generation, and key request for the encryption-decryption process protocol was conducted through formal verification approach using the Scyther Tool. The analysis focuses on aspects of guaranteeing confidentiality of information and authentication with four criteria, namely secrecy, aliveness, synchronization, and agreement. The experimental results showed that these protocols meet the security criteria for the transmitted confidential information but have general weaknesses in the authentication aspect, especially for synchronization and agreement criteria. Based on these weaknesses, technical recommendations are proposed that are able to overcome the identified weaknesses.